2014
DOI: 10.1016/j.jsha.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic cardiomyopathy in the Saudi Arabian population: Clinical and echocardiographic characteristics and outcome analysis

Abstract: The natural history of hypertrophic cardiomyopathy in the Saudi population appears to be benign with catenoid morphology being the most common septal hypertrophy pattern. Risk of SCD appears to be quite low in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Thirty-six per cent of Taiwanese HCM patients had pulmonary oedema or paroxysmal atrial fibrillation. More recently, in the first report on the clinical characteristics of HCM in Saudi Arabia, Ahmed and co-authors found the population of HCM patients to be 71% male, and with a mean age of 42 years 17. Dyspnoea and palpitations were the commonest symptoms, and LVOT obstruction was found in 28%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-six per cent of Taiwanese HCM patients had pulmonary oedema or paroxysmal atrial fibrillation. More recently, in the first report on the clinical characteristics of HCM in Saudi Arabia, Ahmed and co-authors found the population of HCM patients to be 71% male, and with a mean age of 42 years 17. Dyspnoea and palpitations were the commonest symptoms, and LVOT obstruction was found in 28%.…”
Section: Discussionmentioning
confidence: 99%
“…Age at onset of symptoms (38.5 ± 14.3 years), male preponderance (58%), and major symptoms were similar to those reported in North American, Middle Eastern and Eastern series (Table 2). 11,16,17 Nearly 30% of the patients bear mutations in the MYH7 and MYBPC3 genes, which are the commonest genetic causes of HCM 15…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, 55 full-text articles were assessed for eligibility, of which 51 were excluded (25 were irrelevant, 17 were single case reports, 7 were review articles, 1 was an abstract without extractable data, and 1 was a letter to the editor). Three studies [ 16 , 29 , 30 ] and one abstract [ 31 ] were included as they met the inclusion criteria for review. The PRISMA flowchart is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HCM is characterized by hypertrophy of the left ventricle (LVH) in the absence of a secondary cause such as hypertension or aortic stenosis [ 11 , 12 , 14 ]. Clinically, HCM is described to have a very wide variety of presentations ranging from asymptomatic forms to heart failure, with progression to arrhythmia and fibrillation [ 13 , 15 , 16 ]. Consequently, HCM is reported to be the cause of approximately, 50% of sudden cardiac deaths (SCDs) among children, adolescents, and cardiac transplantation patients, as well as among trained athletes [ 12 , 17 - 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been estimated that HCM affects around 20 million people, making this disease the most common genetic cardiovascular disease [5]. Although HCM seems less prevalent among women, both sexes are equally affected [6]. This review presents a systematic approach to the definition, assessment, management and prognosis of patients affected by HCM and their relatives based on current scientific evidence and guidelines.…”
Section: Introductionmentioning
confidence: 99%